Ureaplasma urealyticum upregulates seminal fluid leukocytes and lowers human semen quality: a systematic review and meta-analysis - Omotola SeunFunmi Kukoyi; Victory Jesutoyosi Ashonibare; Cecilia Adedeji Adegbola; Tunmise Maryanne Akhigbe; Roland Eghoghosoa Akhigbe (Basic and Clinical Andrology)
Abstract Background Ureaplasma urealyticum belongs to the class Mollicutes and causes non-gonococcal urethritis, an inflammation of the urethra that is linked with impaired semen quality. However, some reports are contradictory, and the reported effect of U. urealyticum on specific sperm variables is not consistent. Thus, this study synthesized findings from published primary data and provides a robust and reliable inference on the impact and associated mechanisms of U. urealyticum on sperm quality. Methods A systematic search was conducted until 31st May, 2024, on Cochrane, Google Scholar, and Pubmed. The Population, Exposure, Comparator/Comparison, Outcomes, and Study Design (PECOS) model was adopted. The populations were male in their reproductive ages who were infected with Ureaplasma urealyticum and confirmed positive versus the control who were age-matched non-infected or treated, while the outcomes included conventional semen parameters, seminal fluid leucocyte count, and sperm interleukin-6 (IL-6) concentrations, and the studies were either cross-sectional or longitudinal. Results When compared with the control, quantitative analysis demonstrated that U. urealyticum significantly reduced ejaculate volume (SMD 0.33 [95% CI: 0.15, 0.52] p = 0.0004), sperm concentration (SMD 0.47 [95% CI: 0.31, 0.64] p < 0.00001), total sperm motility (SMD 0.73 [95% CI: 0.43, 1.02] p < 0.00001), total motile sperm count (SMD 0.21 [95% CI: 0.17, 0.26] p < 0.00001), normal sperm morphology (SMD 0.88 [95% CI: 0.42, 1.35] p = 0.0002), but increased seminal fluid leukocyte count (SMD -0.82 [95% CI: -1.61, -0.02] p = 0.04). In addition, qualitative analysis revealed that U. urealyticum-positive subjects had significantly higher levels of IL-1β, IL-6, IL-8, TNF-α, peroxidase, leukocytes, neutrophils, CD4 + T cells, and CD8 + T cells in the seminal fluid when compared with the control. Furthermore, higher sperm DNA fragmentation and apoptotic sperm cells were observed in U. urealyticum-positive subjects when compared to the control. Conclusions These findings revealed that U. urealyticum lowers semen quality via the upregulation of seminal fluid leukocytes, elastase, pro-inflammatory cytokines, and DNA fragmentation. However, further studies are required to elucidate the mechanisms underlying the association between U. urealyticum and semen quality decline and to develop effective therapies for this condition.